2006
DOI: 10.2134/jeq2004.0418
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Production Consequences of Using Alum‐Amended Poultry Litter as a Nutrient Source for Corn

Abstract: Field trials were established to compare alum-treated poultry litter (ATPL), normal poultry litter (NPL), and triple superphosphate (TSP) as fertilizer sources for corn (Zea mays L.) when applied at rates based on current litter management strategies in Virginia. Trials were established in the Costal Plain and Piedmont physiographic regions near Painter and Orange, VA, respectively. Nitrogen-based applications of ATPL or NPL applied at rates estimated to supply 173 kg of plant-available nitrogen (PAN) ha(-1) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 23 publications
8
43
0
Order By: Relevance
“…Poultry manure treatments along the lower level of NPK produced higher values for plant height, leaf area index and biomass of corn and crop grain yield (Boateng et al, 2006). Integration of poultry manure with synthetic chemical fertilizers can enhance the efficiency of nutrients uptake and availability to crop plant (Warren et al, 2006). Chemical fertilizers have deleterious effect on soil fertility, while integration of chemical fertilizers with organic manures and bio-fertilizers would be able to maintain soil fertility and sustain crop productivity (Jeyabal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry manure treatments along the lower level of NPK produced higher values for plant height, leaf area index and biomass of corn and crop grain yield (Boateng et al, 2006). Integration of poultry manure with synthetic chemical fertilizers can enhance the efficiency of nutrients uptake and availability to crop plant (Warren et al, 2006). Chemical fertilizers have deleterious effect on soil fertility, while integration of chemical fertilizers with organic manures and bio-fertilizers would be able to maintain soil fertility and sustain crop productivity (Jeyabal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, plant growth has been restricted due to aluminium toxicity by phosphorus deficiencies induced by the ability of alum to adsorb phosphorus in soil medium and convert it into forms unavailable for plant growth [22]; [6]. In addition, root cells show sensitivity to Al 3+ toxicity by a reduction in lateral root size [24]; [3]. This reduction in the activity of the root cells may be due to reduction in both new cell formation and cell elongation in the extension region of the root [25].…”
Section: Resultsmentioning
confidence: 99%
“…Aluminium toxicity is one of the major factors that can limit the growth and development of plants in acidic growth medium, such that root cells and plasma membrane are seriously affected [26]; [27]. Strong interaction of Al which is the main Al toxic form with oxygen donor ligand results in the inhibition of cell division, cell extension and transport [3]. In addition, at the cellular and molecular level, many cells components are implicated in Al toxicity including DNA in nucleus, numerous cytoplasmic components and mitochondria [27]; [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poultry manure application registered over 53% increases of N level in the soil, from 0.09% to 0.14% and exchangeable cations increase with manure application [11]. In agriculture, the main reasons for applying poultry manure include the organic amendment of the soil and the provision of nutrients to crops [12]. An experiment conducted by Amanullah et al [13] indicated that application of poultry manure registered higher uptake of NPK than control in cassava.…”
Section: Introductionmentioning
confidence: 99%